Studying the Kazakhstan and Bulgaria global competitiveness by WEF, IMD, WB indicators - Kaster Sarkytkan, Azamat Baitassov,; Dimitrova Sabeva, Petya (Opción, 2019)
In this article we will take a detailed look and do a comparative analysis, identifying the weaknesses and competitive advantages of Kazakhstan and Bulgaria in terms of the World Economic Forum, the International Institute for Management Development and the World Bank. As a result, Bulgaria’s high competitiveness is associated, firstly, with the good development and implementation of information and communication technologies and a good innovative level. In conclusion, it is important to constantly monitor and track trends in the world and the country in terms of competitiveness, which allow identifying strengths and weaknesses, threats and opportunities, and take appropriate response measures